Financial Education for low-income women: a parallel to Social and Collaborative Economy - Nascimento, Thiago Godoy (Brazilian Journal of Operations & Production Management, 2018)
The understanding of the daily financial habits of low-income women, specifically the beneficiaries of the Bolsa Família Program, is the starting point of a field study conducted by the Brazilian Financial Education Association (AEF-Brasil), organization that operates the National Strategy Financial Education, federal state policy. The understanding of such habits led to the development of educational social technology for this vulnerable public, aiming to improve their behavior in relation to money, especially the planning and the pursuit of the realization of dreams. It is related to understanding how such Technology would impact the lives of these women and their families, as well as on the engagement and reflection on the role of the Social and Collaborative Economy in the new economic arrangements, especially among populations that are on the margins of the consumer society.